Valid for Who? A Preliminary Investigation of the Validity of Two Sexual Victimization Questionnaires in Men and Sexual Minorities - Anderson, Rae Ann E. (American journal of criminal justice, 2021)
The #MeToo movement illuminated vast numbers of people who experienced sexual violence, but the exact scope and impact, especially among under-studied populations (e.g., men and sexual minorities) is unclear, due in part to measurement issues. Our objective was to compare the validity of two measures of sexual violence victimization: The Sexual Experiences Survey – Short Form Victimization (SES-SFV) and The Post-Refusal Sexual Persistence Scale – Victimization (PRSPS-V). Participants were 673 college students who first completed the Rape Empathy for Victims (REM-V) and then the SES-SFV and PRSPS-V (counter-balanced). We found strong evidence of convergent validity for the PRSPS-V with correlations ranging from r = .57–88. Convergent validity correlations were strongest for sexual minority women ( r = .88) and weakest for heterosexual men ( r = .57). We also found evidence of differential validity for the SES-SFV and PRSPS-V. For heterosexual women, rape empathy was correlated to victimization on both questionnaires ( r = .25–.29). However, for heterosexual men, only scores on the SES-SFV were correlated with rape empathy for victims ( r = .19). For sexual minorities there appeared to be differences between PRSPS-V only victims and those who reported victimization on both questionnairnes in rape empathy ( F = 2.65, p = .053). These results provide researchers a starting point for improving these questionnaires to collect more accurate data that helps improve the ability to detect cases of sexual victimization and thus, prevent and heal sexual victimization, especially in understudied populations such as men and sexual minorities.